Impact of the angular position of individual body segments of a shot putter in the projection onto the X-axis to the distance of the shot range - Biberovic, A.; Zeljkovic, M.; Dzibric, D.; Saracevic, Z.; Huremovic, T. (Sports Science and Health, 2015)
The study was conducted with the objective to determine the impact of the angular position of individual body segments in the projection onto the x-axis to the distance of the shot range. It was conducted on one individual who is Bosnia and Herzegovina`s national team shot putter Hamza Alic. The selection of variables was adjusted to the sample of the examinee which was specific in the study and which was conditioned by placing sensors on the examinee`s individual body segments during the recording. For determining kinematic parameters, A = acceleration of shot putter`s individual body segments in the x-axis, 22 variables were applied (predictor group) and criterion variable for calculating kinematic parameters of the shot putter which is made up of the distance of the shot range (36 proper throws). On the basis of the results gathered in regression analysis it can be inferred that by increasing the angle of the right and left elbow as well as left knee, the distance of the achieved result in throwing a shot put is increased.